Evaluación de los posgrados de la Facultad de Odontología de la Universidad de Antioquia entre 1982 y 1995 (desempeño y grado de satisfacción)* - Ossa-de D., Nury; Gualdrón-M., Carmen Sofía (Revista Facultad de Odontología Universidad de Antioquia, 2017)
In the investigation "Evaluation of the graduate studies of the Faculty of Dentistry of the University of Antioquia between 1982 and 1995", 83% of the graduates participated. In relation to performance and degree of satisfaction it was found that once the students graduated their laboral performance was closely related with two of the objectives proposed in their formation as post- graduates, the clinical and teaching aspects. In the clinical area, the private practice prevailing. The degree of satisfaction as to the formation recieved was between 81 and 95%. The satisfaction was closely related to their expectations in the clinical formation. As to the little, it was found that problems existed in the recognition from the laboral associations and some employers. But in the interview the mayor employers in the city of Medellin reported that there was no difference between the graduates of the University of Antioquia and the graduates of other educational centers.